Dampak Perang Dagang Amerika Serikat Vs Cina Dalam Ekonomi Syariah - Prasetyo, Totok Adhi; Ardeliana, Adna Fika Abidah; Sarniati, Sarniati; DG. Mallimpo, Ainun Putri; Supardi, Andi (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This research explores the ramifications of the trade conflict between the United States and China on the Islamic economy, examining both direct consequences through trade and investment avenues and indirect effects via shifts in market sentiment, commodity values, and capital flows. The investigation targets key sectors within the Islamic economic framework, such as the halal industry, Islamic banking, and Sharia-compliant investment vehicles. Furthermore, the study assesses how national policy structures can be optimized to bolster the Islamic economy amidst global uncertainties. Employing a descriptive qualitative methodology and leveraging secondary data from diverse national and international official documents and publications reveals that the US-China trade dispute has significantly influenced Indonesia's market and associated industries. This trade tension has fostered investor apprehension, triggered volatility in commodity prices, and exerted downward pressure on the Rupiah's exchange rate. Export-oriented sectors, including agriculture and energy, have directly experienced the repercussions of diminished global demand and fluctuating commodity prices. Nevertheless, the Islamic economy exhibits inherent resilience, largely attributable to its principles of transparency and prudence. This situation underscores the critical need for governmental interventions to foster the expansion of Indonesia's economy, which includes strategies for diversifying export markets and offering incentives to Islamic-based enterprises.